Model based framework for measuring service level agreement performance in service oriented architecture - Ahmad Al-Sakkaf, Alawi Abdullah (2013)
Service-Oriented Architecture (SOA w) hich managesre mote servic eunder a third party or provide ris a new paradigm for building IT system.s In SOA, the increasing demand f ocrross-organizational service shas highlighted the need for Service-level Agreement (SLA)a nd monitoring o fits service level (performanc.e ) Although the role of machine-readable SLA languages like Web Service Level Agreemen t(WSLA) is recognized ,but, the engineering of monitors is complex becauseit uses th ecode-baseda pproach.T herefore, researc hon effective designs of monitors for SOA environment and providing standsa rdin the instrumentation process would improve SOA. This thesis proposde a mode-lbased engineering approacht o raise the abstraction and- urese levels for designings tandard monitors with automation support. Model Drivenr cAhitecture( MDA) was used to automate the development of the software produc t(monitor). This was don eby mapping a business model called Platform Independent M o(dPeIMl ) into Platform Specific Model (PSM)u sing Query View Transform (QVT) as thes tandard languag. eIn this approach the PIM metamodel is stemmed from WSLA while the PSM is borrowed from SEI framework .Model-based testin gwas used to generate tests as an artifact which is a requirement fort he 6-element framework. Asa design science resear, ch an email system case stu dwyas used to evaluate eth framework. The results shoewd that Mode-lbased engineerin pgrovided a standard metho fdor developing monitor s that has raised the abstraction and eventually led to a maintainable and reusable framework. PSM would also act as the standard implementation model for configuring monitors using QVT because itis effective and could configure a number of monitor sby reusing the same artifac (tpsroposed PIM and PSM) requiring less humanin tervention . Besides thatt,h e PIM metamodel can be exteend dto accept different SLA language sT.he research has proven that the proposoede mls are not only the best means of communication beeetwn SLA stakeholdrse, but are the core engineering assse tfor both human and machineb ecause the ycould reduce engineeringe ffort.